A bimetallic composite pipe with high bonding strength and a preparation method thereof
By using copper-nickel brazing material containing carbon nanotubes at the interface of the bimetal composite tube, combined with cold drawing, rotary vacuum brazing and heat treatment processes, the problems of component gradient in the interface of the bimetal composite tube are solved, and its binding strength and corrosion resistance are significantly improved.
Patent Information
- Application Number
- CN202110915798.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-08-10
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2041-08-10
AI Technical Summary
The existing bimetal composite tubes have component gradients, interface holes, inclusions and precipitation phase defects at the interface, resulting in insufficient interface bonding strength, thereby shortening its service life and restricting its application range.
Copper-nickel brazing material containing carbon nanotubes is used to combine stainless steel liner with carbon steel base tubes through cold drawing, rotary vacuum brazing and heat treatment processes, which significantly reduces pore generation and interface stress during the brazing process, increases the density of the brazing layer, and alleviates the phenomenon of interfacial composition gradient.
It significantly improves the interface bonding strength of the bimetal composite pipe, improves its corrosion resistance and service life, and is suitable for the industrial production of oil and gas field pipelines.
Smart Images

Figure CN115703162B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal pipe processing, and in particular to a bimetallic composite pipe with high bonding strength and a preparation method thereof. Background Art
[0002] As my country's oil and gas field exploitation develops towards "ultra-deep, high temperature, high pressure, and complex working conditions", the corrosion factors in the oil and gas field pipeline transportation environment continue to increase. Extreme corrosion conditions such as high temperature, high pressure, high H2S / CO2 content, and high flow rate can easily cause corrosion of the inner wall of the pipeline and even lead to pipe penetration, causing accidents such as bursting and leakage of in-service pipelines, which seriously threaten the safe operation and transportation of pipelines. The increasingly serious corrosion problem of my country's oil and gas field pipelines urgently needs an effective solution.
[0003] At present, the existing anti-corrosion technologies are mainly divided into two categories: one is external anti-corrosion technology, and the other is pipe body anti-corrosion technology. External anti-corrosion technology mainly includes anti-corrosion coatings and cathodic protection, etc., which realize corrosion protection by physically / chemically isolating corrosive media or sacrificial anodes; however, due to the limitation of coating process, anti-corrosion coatings are easy to fall off, unable to completely isolate corrosive media, and have a short service life; cathodic protection is easy to cause under-protection and over-protection, and the anti-corrosion effect is poor. Compared with external anti-corrosion technology, pipe body anti-corrosion technology mainly focuses on changing the steel structure, such as preparing new corrosion-resistant alloys, bimetallic composite pipe materials, etc. In recent years, bimetallic composite pipes have gradually become one of the important choices for oil and gas field pipeline anti-corrosion due to their excellent anti-corrosion performance, mature preparation technology and controllable production costs. Bimetallic composite pipes prepared by compounding corrosion-resistant alloy pipes with carbon steel pipes can achieve a balance between strength and corrosion performance, overcome the performance defects of a single metal, reduce manufacturing costs, and can adapt to special working conditions and environmental requirements such as complex stress, corrosion and friction. They have broad application prospects in nuclear power, petrochemicals, marine engineering, power electronics, machinery manufacturing, architectural decoration and other fields.
[0004] There are currently two main manufacturing processes for bimetallic composite pipes: mechanical composite and metallurgical composite, including mechanical extrusion, hydraulic expansion, explosive welding, brazing, powder metallurgy, hot extrusion, spray molding and other technologies to form a metallurgical composite interface between the substrate and the cladding. The performance of bimetallic metallurgical composite pipes is closely related to the characteristics of the metallurgical composite interface, such as interface microstructure, precipitation phase, pores, element interdiffusion layer, etc. In the mechanical composite method, the liner and the base pipe are mechanically extruded and combined, and the interface is not tightly bonded, which is prone to stratification and failure. The metallurgical composite method combines the liner and the base pipe by mechanical extrusion, chemical precipitation, spray molding, electromagnetic forming and other methods. This method has a stronger interface bonding force, but the interface still has defects such as composition gradient (decarburization layer on the carbon steel side and carbide layer on the stainless steel side), precipitation phase and pores, resulting in insufficient interface bonding strength, interface corrosion and other problems, thereby shortening its service life and restricting its application range.
[0005] In response to the above problems, at present, domestic and foreign countries have adopted multiple vacuum rolling, optimized heat treatment process and other means to refine the grains at the interface of bimetallic composite tubes, reduce the composition gradient, etc. to improve the interface organization and enhance the interface bonding strength. However, the existing process still cannot effectively reduce the composition gradient, interface holes, inclusions and precipitation phase defects at the interface of bimetallic composite tubes, resulting in frequent failure cases. Summary of the invention
[0006] In view of the problems existing in the prior art, the present invention provides a bimetallic composite pipe with high bonding strength and a preparation method thereof, which can overcome the common shortcomings of composition gradient, interface holes, inclusions and precipitated phases at the interface of the existing bimetallic composite pipes, effectively improve the corrosion resistance and service life of the bimetallic composite pipe, and thereby expand the application scope of the bimetallic composite pipe in my country's oil and gas fields.
[0007] In order to solve the above technical problems, the present invention is implemented by the following technical solutions:
[0008] A method for preparing a bimetallic composite pipe with high bonding strength comprises the following steps:
[0009] Step 1, uniformly coating a copper-nickel brazing filler metal containing carbon nanotubes on the outer surface of a stainless steel liner;
[0010] Step 2, laminating and nesting a stainless steel liner tube coated with a copper-nickel brazing filler metal containing carbon nanotubes in a carbon steel base tube to form a bimetallic composite tube assembly, and performing a cold drawing process on the bimetallic composite tube assembly;
[0011] Step 3, subjecting the bimetallic composite pipe assembly after the cold drawing process to a rotary vacuum brazing process;
[0012] Step 4: heat-treating the bimetallic composite pipe assembly that has been subjected to the rotary vacuum brazing treatment to obtain a bimetallic composite pipe with high bonding strength.
[0013] Furthermore, in step 1, the mass percentage of carbon nanotubes in the copper-nickel solder containing carbon nanotubes is 5% to 50%.
[0014] Furthermore, in step 1, the thickness of the copper-nickel solder containing carbon nanotubes uniformly coated on the outer surface of the stainless steel liner is 10 μm to 50 μm.
[0015] Furthermore, in step 3, the conditions of the rotary vacuum brazing process include: a vacuum degree of 0.2×10 -3 Pa~0.9×10 -3 Pa, the brazing temperature is 900℃~1000℃, the holding time is 2min~40min, and the rotation speed is 10rpm~80rpm.
[0016] Further, in step 4, the heat treatment includes a first stage heat treatment process and a second stage heat treatment process;
[0017] The first stage heat treatment process is: placing the bimetallic composite pipe assembly after the rotary vacuum brazing process into a heat treatment furnace, introducing argon gas, heating to 450°C to 550°C at a rate of 3°C / min to 6°C / min, and keeping the temperature for 40min to 80min;
[0018] The second stage heat treatment process is as follows: after the heat preservation is completed, the temperature is lowered to 50°C to 100°C at a rate of 3°C / min to 6°C / min, the introduction of argon is stopped, and then cooled to room temperature.
[0019] Furthermore, in step 1, before the copper-nickel brazing filler metal containing carbon nanotubes is uniformly coated on the outer surface of the stainless steel liner, the outer surface of the stainless steel liner is surface treated to remove surface impurities and attachments;
[0020] In step 2, before the stainless steel liner tube coated with the copper-nickel solder containing carbon nanotubes is nested in the carbon steel base tube, the inner surface of the carbon steel base tube is treated to remove surface impurities and attachments.
[0021] Furthermore, in step 1, in the copper-nickel solder containing carbon nanotubes, the diameter of the carbon nanotubes is 5 nm to 50 nm, and the length of the carbon nanotubes is 5 μm to 60 μm.
[0022] Furthermore, in step 1, the preparation method of the copper-nickel solder containing carbon nanotubes is:
[0023] The copper-nickel solder containing carbon nanotubes is prepared by vacuum low-speed ball milling of carbon nanotubes, copper-nickel powder and auxiliary fillers, wherein the auxiliary fillers include Sn, B and Fe.
[0024] Furthermore, the stainless steel is 316L stainless steel.
[0025] A bimetallic composite pipe with high bonding strength is prepared by applying the method for preparing the bimetallic composite pipe with high bonding strength. The interface bonding strength of the bimetallic composite pipe with high bonding strength is 600MPa-700MPa.
[0026] Compared with the prior art, the present invention has at least the following beneficial effects:
[0027] The bimetallic composite pipe with high bonding strength of the present invention is prepared by cold drawing, rotary vacuum brazing and heat treatment process of stainless steel liner pipe and carbon steel base pipe by using copper-nickel brazing material containing carbon nanotubes. The rotary vacuum brazing method can realize dynamic welding of copper-nickel brazing material containing carbon nanotubes under vacuum state during brazing, significantly reduce the pores and interface stress generated during brazing, increase the density of brazing layer, and alleviate the composition gradient phenomenon at the interface between carbon steel side and stainless steel side, thereby enhancing the interface bonding strength between stainless steel liner pipe and carbon steel base pipe and improving its anti-corrosion performance, especially anti-pitting performance. Carbon nanotubes have excellent toughening and strengthening effects, which can significantly improve the bonding strength of brazing layer between stainless steel liner pipe and carbon steel base pipe, while carbon nanotubes and copper-nickel are basically non-reactive and have good wettability and thermal conductivity, which can effectively alleviate the shortcomings of composition gradient, interface pores, inclusions and precipitation phases, interface stress, and poor synergistic deformation in the preparation process of existing bimetallic composite pipes, while improving the density of brazing layer, thereby obtaining bimetallic composite pipe with high bonding strength.
[0028] The preparation method of the invention has low production cost, simple process and strong controllability, and is suitable for industrialized production of pipelines for oil and gas fields.
[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are given below and described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions in the specific implementation modes of the present invention, the drawings required for use in the description of the specific implementation modes will be briefly introduced below. Obviously, the drawings described below are some implementation modes of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 This is an interface structure diagram of a bimetallic composite tube with high bonding strength prepared in Example 1;
[0032] Figure 2 This is an interface SEM image of the bimetallic composite tube with high bonding strength prepared in Example 1;
[0033] Figure 3 This is an interface energy spectrum test diagram of the high bonding strength bimetallic composite tube prepared in Example 1;
[0034] Figure 4 This is a bonding strength test diagram of the high bonding strength bimetallic composite tube prepared in Example 1 and a common bimetallic composite tube.
[0035] In the figure: 1-liner; 2-brazing layer; 3-base pipe. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs.
[0038] As used in this article, the term "316L stainless steel" refers to pipeline steel used for oil and gas transportation, and is also the steel used for oil pipes in the American Petroleum Institute standard API. AISI 316L is the corresponding American designation, and sus 316L is the corresponding Japanese designation. my country's unified digital code is S31603, the standard grade is 022Cr17Ni12Mo2 (new standard), the old grade is 00Cr17Ni14Mo2, and the national standard is GB / T 20878-2007.
[0039] As used in this article, the term "carbon steel" refers to pipeline steel used for oil and gas transportation. It is also the oil pipe steel in the American Petroleum Institute standard API. The national standard is GB / T 9711. It is a commonly used pipeline material for surface gathering and transportation pipelines in oil and gas fields.
[0040] As used herein, the term "sccm" is a unit of volume flow, ie, standard-state cubic centimeter per minute.
[0041] The present invention provides a method for preparing a bimetallic composite pipe with high bonding strength, comprising the following steps:
[0042] Step 1: evenly coat the copper-nickel brazing material containing carbon nanotubes on the outer surface of the stainless steel liner.
[0043] Preferably, the stainless steel is 316L stainless steel.
[0044] Preferably, before the copper-nickel solder containing carbon nanotubes is uniformly coated on the outer surface of the stainless steel liner, the outer surface of the stainless steel liner is surface treated to remove surface impurities and attachments; specifically, the surface impurities and attachments of the stainless steel liner are first cleaned with a steel brush, and then the stainless steel liner is cleaned and dried with alcohol, acetone or deionized water or a combination thereof, and the cleaning is ultrasonic cleaning, the ultrasonic cleaning time is 40-60 minutes, the drying temperature is 30°C to 60°C, preferably 40°C to 50°C, and the drying time is 30min to 60min, preferably 40min to 50min.
[0045] Preferably, the preparation method of the copper-nickel solder containing carbon nanotubes is: carbon nanotubes, copper-nickel powder and auxiliary fillers are prepared by vacuum low-speed ball milling to obtain the copper-nickel solder containing carbon nanotubes, and the auxiliary fillers include Sn, B and Fe; specifically, the ball milling process uses a grinding ball with a diameter of 6 mm, a material-to-ball ratio of 3:1, and the ball milling speed is 200 rpm for 2 hours to obtain the copper-nickel solder containing carbon nanotubes.
[0046] Preferably, in the copper-nickel solder containing carbon nanotubes, the mass percentage of carbon nanotubes is 5% to 50%, preferably 10% to 30%, and more preferably 15% to 25%.
[0047] Preferably, in the copper-nickel solder containing carbon nanotubes, the diameter of the carbon nanotubes is 5 nm to 50 nm, preferably 10 nm to 20 nm; the length of the carbon nanotubes is 5 μm to 60 μm, preferably 10 μm to 40 μm.
[0048] Preferably, the thickness of the copper-nickel brazing filler metal containing carbon nanotubes uniformly coated on the outer surface of the stainless steel liner is 10 μm to 50 μm, preferably 12 μm to 35 μm, and more preferably 15 μm to 25 μm.
[0049] Step 2: fit and nest the stainless steel liner tube coated with copper-nickel solder containing carbon nanotubes in the carbon steel base tube to form a bimetallic composite tube assembly, and perform cold drawing on the bimetallic composite tube assembly. Specifically, the bimetallic composite tube assembly is placed in a cold drawing device for cold drawing.
[0050] Preferably, before the stainless steel liner coated with copper-nickel solder containing carbon nanotubes is fitted and nested in the carbon steel base pipe, the inner surface of the carbon steel base pipe is surface treated to remove surface impurities and attachments; specifically, the surface impurities and attachments of the carbon steel base pipe are first cleaned with a steel brush, and then the carbon steel base pipe is cleaned and dried with alcohol, acetone or deionized water or a combination thereof, and the cleaning is ultrasonic cleaning, the ultrasonic cleaning time is 40-60 minutes, the drying temperature is 30°C to 60°C, preferably 40°C to 50°C, and the drying time is 30min to 60min, preferably 40min to 50min.
[0051] In the present invention, the carbon steel is pipeline carbon steel, low alloy steel or carbon steel for pressure vessels.
[0052] Step 3: subjecting the bimetallic composite pipe assembly after the cold drawing process to a rotary vacuum brazing process, specifically, subjecting the bimetallic composite pipe assembly to a rotary vacuum brazing process in a rotary vacuum brazing furnace.
[0053] Preferably, the conditions for the rotary vacuum brazing process include: introducing protective gas into the rotary vacuum brazing furnace to adjust the vacuum degree of the vacuum brazing to 0.2×10 -3 Pa~0.9×10 -3 Pa, preferably 0.6×10 -3 Pa~0.8×10 -3 Pa; the brazing temperature is 900℃~1000℃, preferably 920℃~980℃, more preferably 930℃~960℃; the holding time is 2min~40min, preferably 5min~30min, more preferably 10min~25min; the rotation speed is 10 rev / min~80 rev / min, preferably 15 rev / min~70 rev / min, more preferably 20 rev / min~35 rev / min.
[0054] More preferably, the protective gas is argon, helium or hydrogen or a combination thereof, and the protective flow rate is 800 sccm to 1500 sccm. Preferably, the protective gas is hydrogen and argon, the flow rate of hydrogen is 500 sccm to 700 sccm, the flow rate of argon is 300 sccm to 800 sccm, the purity of hydrogen is 99.999%, and the flow rate of argon is 99.99%.
[0055] Step 4: heat-treating the bimetallic composite pipe assembly that has been subjected to the rotary vacuum brazing treatment to obtain a bimetallic composite pipe with high bonding strength.
[0056] Preferably, the heat treatment includes a first stage heat treatment process and a second stage heat treatment process, which are specifically as follows:
[0057] The first stage heat treatment process is as follows: the bimetallic composite pipe assembly after the rotary vacuum brazing treatment is placed in a heat treatment furnace, argon gas with a flow rate of 500 sccm is introduced, the temperature is raised to 450°C to 550°C at a rate of 3°C / min to 6°C / min, and the temperature is kept for 40min to 80min;
[0058] The second stage heat treatment process is: after the insulation is completed, the temperature is lowered to 50℃~100℃ at a rate of 3℃ / min~6℃ / min, the introduction of argon is stopped, and then cooled to room temperature.
[0059] The high-bonding-strength bimetallic composite tube prepared by the preparation method of the high-bonding-strength bimetallic composite tube of the present invention is composed of a stainless steel liner, a brazing layer and a carbon steel base tube from the inside to the outside, and the brazing layer is a copper-nickel brazing material containing carbon nanotubes, that is, the stainless steel liner and the carbon steel base tube are brazed and connected by the copper-nickel brazing material containing carbon nanotubes to form a high-bonding-strength bimetallic composite tube. The interface bonding strength of the high-bonding-strength bimetallic composite tube of the present invention is 600MPa to 700MPa.
[0060] The toughening and strengthening effect of the carbon nanotubes in the copper-nickel brazing material and the high thermal conductivity characteristics are used to enhance the collaborative plastic deformation capabilities of the liner and the base pipe, avoid local stress concentration at the interface, eliminate micropores in the brazing layer, and alleviate the interface composition gradient, thereby achieving high bonding strength between the liner and the base pipe.
[0061] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually based on conventional conditions or the conditions recommended by the manufacturer. Unless otherwise stated, percentages and parts are calculated by weight.
[0062] Example 1
[0063] A method for preparing a bimetallic composite pipe with high bonding strength is as follows:
[0064] S1. Weigh 550g of Cu, 100g of Ni, 40g of Sn, 30g of B, 30g of Fe, and 250g of carbon nanotubes with a diameter of 15nm and a length of 25μm respectively, mix them in a total of 1000g (i.e., the mass percentage of carbon nanotubes is 25%), stir them manually and put them into a vacuum ball mill for ball milling, wherein the grinding ball diameter is 6mm, the material-ball ratio is 3:1, the rotation speed is 200rpm, and the ball milling time is 2 hours to obtain a brazing filler metal for brazing of bimetallic composite tubes with high bonding strength, i.e., a copper-nickel brazing filler metal containing carbon nanotubes.
[0065] S2. Select a seamless carbon steel pipe of a certain size as the base pipe and a 316L stainless steel pipe as the liner pipe. First, use a steel brush to clean the surface of the base pipe and the liner pipe to remove impurities and attachments. Then use alcohol + acetone as the cleaning liquid to ultrasonically clean the two base pipes and the liner pipe for 45 minutes. After cleaning, put the two base pipes and the liner pipe into a vacuum drying oven and dry them at 40°C for 45 minutes for use.
[0066] S3. Coat the copper-nickel brazing filler metal containing carbon nanotubes evenly on the surface of the 316L stainless steel tube body with a coating thickness of about 20 μm; then assemble the carbon steel tube body and the 316L stainless steel tube body to form a bimetallic composite tube assembly, and place it in a cold drawing die, and perform cold drawing after the fixture is assembled.
[0067] S4. Place the cold-drawn bimetallic composite tube assembly into a rotary vacuum brazing furnace, and introduce protective gases of hydrogen and argon. The hydrogen flow rate is 600 sccm and the argon flow rate is 500 sccm. The vacuum degree is controlled to be 0.8×10 -3 Pa; then, the temperature was raised at 5°C / min, and the speed of the brazing material table was adjusted to 30 rpm; when the temperature reached 950°C, the temperature was kept at 950°C for 20 minutes for brazing, and after the brazing was completed, the temperature was cooled to room temperature, and the bimetallic composite pipe assembly after brazing was taken out.
[0068] S5. Put the brazed bimetallic composite pipe assembly into a heat treatment furnace, introduce argon gas with a flow rate of 500 sccm, heat it to 500°C at a rate of 5°C / min, and keep it warm for 60 minutes. After the insulation time is over, cool it to 50°C at a rate of 5°C / min, stop introducing argon gas, and then cool it to room temperature to obtain a bimetallic composite pipe with high bonding strength.
[0069] The bimetallic composite tube obtained in Example 1 was subjected to SEM, EDS and bonding strength tests. The test results are as follows: Figure 2-4 shown.
[0070] Figure 2 This is a SEM image of the interface of the bimetallic composite tube with high bonding strength prepared in Example 1. Figure 2 It shows that the brazing layer of the bimetallic composite tube obtained in Example 1 is dense and uniform, without micropores and precipitation.
[0071] Figure 3 This is the interface EDS result of the high bonding strength bimetallic composite tube prepared in Example 1. Figure 3It shows that the brazing layer of the bimetallic composite tube with high bonding strength obtained in Example 1 is composed of carbon, copper, nickel, boron, tin and iron, among which the copper content is 53.57%, the carbon content is 26.29%, the nickel content is 12.35%, the boron content is 2.62%, the tin content is 2.85% and the iron content is 2.32%.
[0072] Figure 4 This is a bonding strength test diagram of the high bonding strength bimetallic composite tube prepared in Example 1. Figure 4 It is shown that the bonding strength of the high bonding strength bimetallic composite tube obtained in Example 1 is 688 MPa.
[0073] Example 2
[0074] The method is the same as that of Example 1, except that in S1, the carbon nanotube content is 200 g.
[0075] The results show that the bonding strength of the prepared bimetallic composite tube is 642MPa.
[0076] Example 3
[0077] The method is the same as that of Example 1, except that in S3, the solder coating thickness is 10 μm.
[0078] The results show that the bonding strength of the prepared bimetallic composite tube is 629MPa.
[0079] Example 4
[0080] The method is the same as that of Example 1, except that in S4, the temperature is 930°C.
[0081] The results show that the bonding strength of the prepared bimetallic composite tube is 633MPa.
[0082] Example 5
[0083] The method is the same as that of Example 1, except that in S4, the rotation speed of the brazing material table is 20 rpm.
[0084] The results show that the bonding strength of the prepared bimetallic composite tube is 654MPa.
[0085] Comparative Examples 1-4
[0086] The bimetallic composite tube is prepared by using copper-nickel brazing filler metal without carbon nanotubes and a common vacuum brazing method.
[0087] The bimetallic composite tubes described in Comparative Examples 1-4 were prepared in a similar manner to Example 1, except that the parameters in the composite tube preparation process were changed as shown in Table 2, and the bonding strength of the composite tubes was measured in the same bonding strength test method as in Example 1.
[0088] Table 2 Bonding strength performance test of bimetallic composite pipes prepared in Comparative Examples 1-4
[0089]
[0090] The bonding strength of the bimetallic composite tubes prepared in Examples 1-5 and Comparative Examples 1-4 was tested. The results are as follows: Figure 4 shown.
[0091] Depend on Figure 4 It can be seen that the bonding strength of the bimetallic composite tubes prepared in Examples 1-5 (such as Example 1, the bonding strength is 688 MPa) is significantly greater than that of Comparative Examples 1-4 (such as Comparative Example 4, the bonding strength is 472 MPa). Therefore, compared with Comparative Examples 1-4, the bimetallic composite tubes prepared in Examples 1-5 of the present invention have high bonding strength.
[0092] Example 6
[0093] The method is the same as that of Example 1, except that in S1, the diameter is 5 nm and the length is 10 μm; in S3, the solder coating thickness is 12 μm.
[0094] The results show that the bonding strength of the prepared bimetallic composite tube is 645MPa.
[0095] Example 7
[0096] The method is the same as that of Example 1, except that in S1, the diameter is 10 nm and the length is 40 μm; in S3, the solder coating thickness is 15 μm.
[0097] The results show that the bonding strength of the prepared bimetallic composite tube is 636MPa.
[0098] Example 8
[0099] The method is the same as that of Example 1, except that in S1, the diameter is 20 nm and the length is 5 μm; in S3, the solder coating thickness is 25 μm.
[0100] The results show that the bonding strength of the prepared bimetallic composite tube is 657MPa.
[0101] Example 9
[0102] The method is the same as that of Example 1, except that in S1, the diameter is 50 nm and the length is 60 μm; in S3, the solder coating thickness is 35 μm.
[0103] The results show that the bonding strength of the prepared bimetallic composite tube is 663MPa.
[0104] Example 10
[0105] The method is the same as that of Example 1, except that in S1, the diameter is 30 nm and the length is 50 μm; in S3, the solder coating thickness is 50 μm.
[0106] The results show that the bonding strength of the prepared bimetallic composite tube is 660MPa.
[0107] Embodiment 11
[0108] The method is the same as in Example 1, except that in S4, the temperature is 900°C, the temperature is kept for 5 min, and the vacuum degree is 0.6×10 - 3 Pa, the rotation speed is 10 rpm.
[0109] The results show that the bonding strength of the prepared bimetallic composite tube is 651MPa.
[0110] Example 12
[0111] The method is the same as in Example 1, except that in S4, the temperature is 920°C, the temperature is kept for 2 min, and the vacuum degree is 0.6×10 - 3 Pa, the rotation speed is 15 rpm.
[0112] The results show that the bonding strength of the prepared bimetallic composite tube is 661MPa.
[0113] Embodiment 13
[0114] The method is the same as in Example 1, except that in S4, the temperature is 960°C, the temperature is kept for 10 min, and the vacuum degree is 0.2×10 -3 Pa, the rotation speed is 35 rpm.
[0115] The results show that the bonding strength of the prepared bimetallic composite tube is 650MPa.
[0116] Embodiment 14
[0117] The method is the same as in Example 1, except that: in S4, the temperature is 980°C, the temperature is kept for 25 min, and the vacuum degree is 0.9×10 -3 Pa, the rotation speed is 60 rpm.
[0118] The results show that the bonding strength of the prepared bimetallic composite tube is 657MPa.
[0119] Embodiment 15
[0120] The method is the same as in Example 1, except that in S4, the temperature is 1000°C, the temperature is kept for 40 min, and the vacuum degree is 0.5×10 -3 Pa, the rotation speed is 70 rpm.
[0121] The results show that the bonding strength of the prepared bimetallic composite tube is 658MPa.
[0122] Example 16
[0123] The method is the same as in Example 1, except that in S4, the temperature is 1000°C, the temperature is kept for 30 min, and the vacuum degree is 0.7×10 -3 Pa, the rotation speed is 80 rpm.
[0124] The results show that the bonding strength of the prepared bimetallic composite tube is 655MPa.
[0125] Embodiment 17
[0126] The method is the same as that in Example 1, except that: in S5, the temperature is raised to 550°C at a rate of 3°C / min and kept at that temperature for 40 min; and the temperature is lowered to 80°C at a rate of 6°C / min.
[0127] The results show that the bonding strength of the prepared bimetallic composite tube is 654MPa.
[0128] Embodiment 18
[0129] The method is the same as that in Example 1, except that: in S5, the temperature is raised to 450°C at a rate of 6°C / min and kept at that temperature for 80 min; and the temperature is lowered to 100°C at a rate of 3°C / min.
[0130] The results show that the bonding strength of the prepared bimetallic composite tube is 656MPa.
[0131] Embodiment 19
[0132] The method is the same as that of Example 1, except that in S1, the carbon nanotube content is 39.4 g.
[0133] The results show that the bonding strength of the prepared bimetallic composite tube is 658MPa.
[0134] Embodiment 20
[0135] The method is the same as that of Example 1, except that in S1, the carbon nanotube content is 83.3 g.
[0136] The results show that the bonding strength of the prepared bimetallic composite tube is 670MPa.
[0137] Embodiment 21
[0138] The method is the same as that of Example 1, except that in S1, the carbon nanotube content is 132.4 g.
[0139] The results show that the bonding strength of the prepared bimetallic composite tube is 672MPa.
[0140] Embodiment 22
[0141] The method is the same as that of Example 1, except that in S1, the carbon nanotube content is 321.4 g.
[0142] The results show that the bonding strength of the prepared bimetallic composite tube is 663MPa.
[0143] Embodiment 23
[0144] The method is the same as that of Example 1, except that in S1, the carbon nanotube content is 750 g.
[0145] The results show that the bonding strength of the prepared bimetallic composite tube is 664MPa.
[0146] Finally, it should be noted that the above-described embodiments are only specific implementations of the present invention, which are used to illustrate the technical solutions of the present invention, rather than to limit them. The protection scope of the present invention is not limited thereto. Although the present invention is described in detail with reference to the above-described embodiments, ordinary technicians in the field should understand that any technician familiar with the technical field can still modify the technical solutions recorded in the above-described embodiments within the technical scope disclosed by the present invention, or can easily think of changes, or make equivalent replacements for some of the technical features therein; and these modifications, changes or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention, and should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.
Claims
1. A method for preparing a bimetallic composite tube with high bonding strength, characterized in that: The following steps are involved: Step 1, uniformly coating a copper-nickel solder containing carbon nanotubes on the outer surface of a stainless steel liner tube, with a coating thickness of 10 μm to 50 μm; in the copper-nickel solder containing carbon nanotubes, the mass percentage of carbon nanotubes is 5% to 50%, the diameter of the carbon nanotubes is 5nm to 50nm, and the length of the carbon nanotubes is 5µm to 60µm; The preparation method of the copper-nickel solder containing carbon nanotubes is as follows: The copper-nickel solder containing carbon nanotubes is prepared by vacuum low-speed ball milling of carbon nanotubes, copper-nickel powder and auxiliary fillers, wherein the auxiliary fillers include Sn, B and Fe; Step 2, laminating and nesting a stainless steel liner tube coated with a copper-nickel brazing filler metal containing carbon nanotubes in a carbon steel base tube to form a bimetallic composite tube assembly, and performing a cold drawing process on the bimetallic composite tube assembly; Step 3, subjecting the cold-drawn bimetallic composite pipe assembly to a rotary vacuum brazing process in a rotary vacuum brazing furnace, wherein the conditions for the rotary vacuum brazing process include: a vacuum degree of 0.2×10 -3 Pa ~0.9×10 -3 Pa, brazing temperature is 900℃~1000℃, holding time is 2 min~40min, rotation speed is 10 rpm~80 rpm; Step 4, heat treating the bimetallic composite pipe assembly that has been subjected to rotary vacuum brazing treatment to obtain a bimetallic composite pipe with high bonding strength, wherein the heat treatment includes a first-stage heat treatment process and a second-stage heat treatment process; the first-stage heat treatment process is: placing the bimetallic composite pipe assembly that has been subjected to rotary vacuum brazing treatment in a heat treatment furnace, introducing argon gas, heating the temperature to 450°C~550°C at a rate of 3°C / min~6°C / min, and keeping the temperature for 40 min~80 min; the second-stage heat treatment process is: after the insulation is completed, cooling the temperature to 50°C~100°C at a rate of 3°C / min~6°C / min, stopping the introduction of argon gas, and then cooling to room temperature.
2. The method for preparing a bimetallic composite pipe with high bonding strength according to claim 1, characterized in that: In step 1, before the copper-nickel brazing filler metal containing carbon nanotubes is uniformly coated on the outer surface of the stainless steel liner, the outer surface of the stainless steel liner is surface treated to remove surface impurities and attachments; In step 2, before the stainless steel liner tube coated with the copper-nickel solder containing carbon nanotubes is nested in the carbon steel base tube, the inner surface of the carbon steel base tube is treated to remove surface impurities and attachments.
3. The method for preparing a bimetallic composite pipe with high bonding strength according to claim 1, characterized in that: The stainless steel is 316L stainless steel.
4. A bimetallic composite pipe with high bonding strength, characterized in that: The high-bonding-strength bimetallic composite pipe is prepared by the preparation method of any one of claims 1 to 3, wherein the interface bonding strength of the high-bonding-strength bimetallic composite pipe is 600 MPa to 700 MPa.
Citation Information
Patent Citations
Method for brazing hard alloy and steel with assistance of carbon nano tube
CN105478944A
Electroplating method aiming at metal plating layer hard-to-implement structure and welding method
CN111962119A
Manufacture of bimetallic composite pipe
CN1375362A